Taxpayer response to greater progressivity: Evidence from personal income tax reform in Uganda - Maria Jouste; Tina Kaidu Barugahara; Joseph Okello Ayo; Jukka Pirttilä; Pia Rattenhuber (Helsinki Graduate School of Economics, 2023)
We evaluate a major personal income tax reform in Uganda that came into effect in 2012–13, contributing to the scarce literature on the effects of personal income tax reform on employees' income in a low-income country in Africa. The reform increased the tax-free lower threshold, increased tax rates for higher incomes, and introduced an additional highest tax band for top 1% of income earners. Using the universe of pay-as-you-earn (PAYE) administrative data from the Uganda Tax Authority, we analyse the impact of the reform on reported labour incomes. In the preferred specification, we find very limited support for behavioural reactions. However, heterogeneity analysis reveals that top-income workers in firms handled by ordinary (as opposed to medium or large taxpayer) offices report lower incomes after the reform. We also find suggestive evidence that part of the response may arise from income shifting. The reform managed to raise more revenue and it also led to a limited reduction in after-tax income inequality.
Keywords: C31; H24; O23; 330; personal income tax; Uganda; administrative data; tax reform